1993
DOI: 10.1161/01.cir.88.2.605
|View full text |Cite
|
Sign up to set email alerts
|

Implantation and intermediate-term follow-up of stents in congenital heart disease.

Abstract: BACKGROUND Balloon-expandable stents (Johnson and Johnson Interventional Systems) have been in use for congenital heart disease since late 1989. They have made possible treatment in previously untreatable branch pulmonary artery stenoses and systemic venous stenosis. The purpose of this report is to detail the results and intermediate-term follow-up of stents used for treatment of congenital heart disease. METHODS AND RESULTS Eighty-five patients underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
163
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(176 citation statements)
references
References 3 publications
9
163
0
3
Order By: Relevance
“…They found that the peak pressure gradients decreased (51 +/-24 vs. 16 +/-13 mmHg; p<0.01) and the vessel diameter increased (5 +/-3 vs. 11 +/-4 mm; p<0.01). Subsequent studies [16,17,[48][49][50][52][53][54][55][56][57], including our own [25,50] documented similar results. The results are similar in both post-operative and native BPAS lesions [17].…”
Section: Immediate Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…They found that the peak pressure gradients decreased (51 +/-24 vs. 16 +/-13 mmHg; p<0.01) and the vessel diameter increased (5 +/-3 vs. 11 +/-4 mm; p<0.01). Subsequent studies [16,17,[48][49][50][52][53][54][55][56][57], including our own [25,50] documented similar results. The results are similar in both post-operative and native BPAS lesions [17].…”
Section: Immediate Resultssupporting
confidence: 76%
“…Follow-up studies [17,59,60] of the cohort reported by O'Laughlin et al [48] revealed minimal loss of stent diameter, mild increase in gradient with true stenosis in only 7% of stents. However, 30 of the 31 stents required re-dilatation either due to development of severe stenosis (7%), residual waist (33%) or limited dilatation at the time of initial stent implantation (60%).…”
Section: Follow-up Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…(53,57) (58,59) These narrowed parts of the Fontan circuit would typically be addressed in the catheter laboratory with balloon dilatation or stent implantation in the older child and adult. (30,(60)(61)(62) …”
Section: Thromboembolismmentioning
confidence: 99%